A Study On Health-Related Quality of Life Among The Stroke Patients In A Tertiary Care Hospital, Mangalore - Nesan, G Shiny Chrism Queen; Kundapur, Rashmi (Journal of Health and Allied Sciences NU, 2018)
Introduction : Stroke is a leading cause of death and acquired human disability in India. One dimension that is rarely measured, is health-related quality of life (HRQOL) which aims to assess the impact of disease from the perspective of the patient.Objectives : To study the health-related quality of life among stroke patients within 3 months of stroke.Materials & Methods : A hospital based study conducted on 20 stroke patients from the registry. The patients with fresh stroke attack and those who were attending the follow up within the first 3 months of the attack were enrolled in the study. Basic demographic data and the data of stroke outcomes were taken. HRQOL was evaluated using the Indian version of the Medical Outcomes Study 36 item Short-Form Health Survey (SF-36). Frequency and percentages were calculated.Results: It was seen that majority (55%) of patients expressed a fair physical domain post stroke. About 40% were of opinion that their physical domain was poor and the rest said that it was good (5%). Assessing the psychological domain, majority of the patients said it was poor. Of the 20 patients, 15 (75%) of them were scaled to have poor social domain and the rest (25%) said it was fair. About half (50%) of the patients showed that they had poor environmental domain. About 15% of them said that it was good. Majority (60%) of the patients had poor general health status.
Keywords: Stroke; Quality of life; physical and psychological domains